ANALISIS LAPORAN GRAFIK BARBER JOHNSON DALAM MENUNJANG PELAPORAN YANG EFEKTIF DAN EFISIEN DI RSUD KANJURUHAN KABUPATEN MALANG - Mohammad Arief Rachman; Dhea Ratnasari Al-Rachmah; Femy Anggryani (JRMIK, 2023)
Background: Hospital reporting is a health service activity in a hospital that has the task of collecting data, processing data, and presenting data into information.Objective : The purpose of hospital reporting is to produce data or information quickly, precisely, andaccurately.Methods : This study uses a quantitative method with a descriptive approach. This study aims to analyze the use of the Barber Jhonson Graph report at Kanjuruan Hospital, Malang Regency, after analyzing that in the evaluation of the inpatient indicator report, the results of the Barber Jhonson graph did not refer to the results of the Barber Jhonson graph, due to lack of knowledge of the reporting section in making Barber Jhonson Graph.Results : Then from the analysis of Barber Johnson's data sources, namely the recapitulation of the inpatient census data and also the daily inpatient census, the calculation of the length of stay did not meet the specified standard. If the patient enters and leaves on the same day, the value is 1, but the calculation of the SIMRs at Kanuruan Hospital, the calculation of the length of time treated by patients entering and leaving on the same day is 0. If the calculation of the length of stay is not immediately justified, the data on the inpatient indicator report has not been said to be efficient. and also in using the results of the inpatient indicator report it is less effective if it does not display the Barber Johnson Graph. The results of the calculation of the inpatient census recapitulation data parameters, namely, BOR, ALOS, TOI, and BTO.Conclusion : The four parameters found BOR below the ideal number. Therefore, the suggestion that the researcher gives is the need for good team coordination between the medical recorder as part of data collection and management as well as the IT team as a supporter of data presentation. So as to produce reports of hospitalization indicators that are accurate and with integrity.Keywords : Barber Johnson, Inpatient, Hospital